The first metamorphosis: the cosmogony of Ovid and the image of the poet in the light of the theories of W. Burkert (Circe de clásicos y modernos, 2018)
Ovid’s epic poem, a mythical and etiologic world history, starts with a story about the origin of the world, followed by the creation of man. Thus, the first metamorphosis is the transformation of chaos into cosmos. The text continues with a description of the decreasing Ages, since “the establishment of a harmonious order is always followed by its dissolution” (HOLZBERG 2002: 120). This work intends to study ovidian cosmogony and anthropogony starting from specific categories set out by W. BURKERT (1999: 87-106) and explore the relationship between what has been termed “technomorphic” character of cosmogony and the figure of the poet itself.
Keywords: cosmology; cosmogony; anthropogony; metamorphosis; survival